A Community of Interest—Victorian Scholars and Literary Societies - Bailin, Miriam (Romanticism and Victorianism on the Net, 2009)
AbstractSingle-author literary societies were formed in the late 1800's by enthusiasts who sought to promote the work and preserve the effects of contemporary or near-contemporary British authors. Though often mocked for their cult-like devotion, these societies filled a gap in the academic study of modern authors when the ancient universities were still debating whether English studies constituted a legitimate discipline. Unfazed by established canons of literary value, society members presented papers, compiled and published bibliographies, produced scholarly editions, and acquired manuscripts and literary relics which might otherwise have gone into private collections. This article briefly rehearses the history of these societies and their continued development with an emphasis on the sometimes awkward, sometimes productive relations between the professional and the general reader.